Dual HER2 blockade with pertuzumab (P) and trastuzumab (T) in patients with HER2-positive metastatic breast cancer (mBC) relapsing after adjuvant treatment with T: results from a German non-interventional study (NIS) HELENA (NCT01777958) - Thill, Marc; Wimberger, Pauline; Grafe, Andrea; Klare, Peter; Luedtke-Heckenkamp, Kerstin; Reichert, Dietmar; Zaiss, Matthias; Ziegler-Löhr, Katja; Eckl, Tanja; Schneeweiss, Andreas (Breast cancer research and treatment, 2022)
NIS HELENA documented outcomes in clinical routine practice of first-line therapy with P plus T and docetaxel (D) of patients with advanced HER2-positive BC and prior (neo)adjuvant T.
Gesehen am 27.06.2023